ANALISIS MANAJEMEN STRATEGI DALAM PENGEMBANGAN MUTU PEMBELAJARAN DI KABUPATEN POLEWALI MANDAR (STUDI MULTISITUS PADA SMP NEGERI 1 CAMPALAGIAN DAN MTS NEGERI 1 POLEWALI MANDAR ) - Sitti Umrawati; Wahira; Hasan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of strategic management in developing learning quality at SMP Negeri 1 Campalagian and MTs Negeri 1 Polewali Mandar, Polewali Mandar Regency. The research aims to describe how strategic management is implemented and to identify the supporting and inhibiting factors affecting its implementation in improving learning quality. A qualitative approach with a multisite study design was employed. Data were collected through observations, interviews, and document analysis involving school principals, vice principals, teachers, and educational staff. Data analysis was conducted through data reduction, data display, conclusion drawing, and cross-site analysis. The findings reveal that both institutions implement strategic management through five main stages: establishing learning quality goals and targets, adjusting organizational structures and role distribution, allocating resources, communicating strategies, and monitoring performance. SMP Negeri 1 Campalagian focuses on school self-evaluation, literacy and numeracy improvement, gradual learning digitalization, and academic supervision, while MTs Negeri 1 Polewali Mandar emphasizes teacher readiness, religious habituation programs, ICT development, bilingual programs, MGMP activities, and classroom supervision. Supporting factors include leadership commitment, teacher competence, stakeholder support, positive work culture, and adequate facilities. Meanwhile, limited resources, inadequate digital infrastructure, uneven student motivation, varying technological competencies among teachers, and limited parental involvement remain significant challenges. The study concludes that consistent implementation of strategic management contributes to improving teacher competence, learning effectiveness, student engagement, and the utilization of educational facilities, thereby enhancing overall learning quality.